SURFACE HARDNESS EVALUATION OF BULK-FILL COMPOSITE RESIN AFTER IMMERSION IN PROBIOTIC DRINKS AND CARBONATED DRINKS - Rema Rufaidah Qisthi; Isyana Erlita; Debby Saputera (FKG Unlam, 2019)
Background: Probiotic drinks and carbonated drinks can affect the surface hardness of bulk-fill composite resin due to its acidic property. The acid may interfere with matrix and filler bonding in composite resin and will result in the dissolution of resin matrix and the decrease in hardness value of bulk-fill composite resin surface. Objective: The purpose of this study was to analyze the differences in bulk-fill composite resin surface hardness after the submergence in probiotic drinks and carbonated drinks. Methods: This study used pure laboratory experimental method (true experimental) with a post-test only and control group design. One Way ANOVA test followed by the Bonferroni Post Hoc test was performed to analyze the significance from each treatment. A total of 27 samples was divided into 3 groups, namely group 1 of bulk-fill composite resin soaked in probiotic drinks, group 2 soaked in carbonated drinks and group 3 soaked in sterile distilled water. The measurement of sample surface hardness was using Vickers Microhardness Tester. Results: The average value of surface hardness in group 1 was 61.41 Kg / mm2, group 2 was 57.62 Kg / mm2 and group 3 was 65.85 Kg / mm2. The results of One Way ANOVA parametric test obtained p = 0,000 (p <0.05) and continued with Bonferroni Post Hoc test which showed significant differences between each group (p<0.05). Conclusion: There is a lower effect of bulk-fill composite resin submergence in probiotic drinks on surface hardness than those immersed in carbonated drinks.